EXPLORING THE USE AND TYPES OF FIGURATIVE LANGUAGE (Web of Teachers: Inderscience Research, 2024)
This article considered when and how to use figurative language in written and spoken language. The author of the article presented brief information about the six types of figurative language, including simile, metaphor, personification, idiom, symbolism, and hyperbole. Some examples of these types were also analyzed.